Pengembangan Media Pembelajaran Smart Box untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan Materi Pancasila, Norma dan Aturan Serta Hak dan Kewajiban Kelas III di SD Negeri 79 Palembang - Rodhiyah, Nyayu Hujjatur; Arni, Yusni; Astriani, Mela; Kasari, Dewi Santi; Selinayanti, Desti (Pusdikra-Publishing.com, 2025)
This study intends to characterize the comprehension of Pancasila Education among fourth grade students at SD Negeri 79 Palembang prior to the introduction of Smart Box media, ascertain whether Smart Box media is beneficial in enhancing students' comprehension, and examine the variables that affect its learning efficacy. It is anticipated that this research will yield both theoretical and practical advantages. The study will theoretically contribute to the body of knowledge on the use of interactive media in education, particularly Pancasila Education, and offer empirical evidence regarding the efficacy of Smart Box media in enhancing students' cognitive capacities. Practically, this study can offer innovative and effective learning methods for teachers, improve students' understanding of Pancasila Education, and be a reference for schools in developing more interesting and effective curriculum and learning methods.